소포성 갑상샘 유두암종의 세침흡인 세포검사의 정확도와 Galectin-3 면역염색의 유용성 - 정찬권; 신정하; 이현승; 이아원; 정은선; 최영진; 이교영; Jung, Chan-Kwon; Shin, Jung-Ha; Lee, Hyun-Seung; Lee, Ah-Won; Jung, Eun-Sun; et al. (Taehan Sepo Pyŏngri Hakhoe chi, 2008)
The cytologic diagnosis of the follicular variant of papillary thyroid carcinoma (FVPTC) has become one of the common causes of false negative diagnoses when performing fine needle aspiration cytology (FNAC) of the thyroid gland. We retrospectively reviewed all the aspirates for which a diagnosis of FVPTC had been made based on the surgically excised specimens, regardless of the cytologic diagnosis. 145 FNACs was performed in 135 patients. The cytologic diagnoses were categorized as 2 unsatisfactory specimens (1.4%), 16 benign (11.0%), 49 atypical (33.8%) and 78 malignant lesions (53.8%). The tumor cells consistently showed significant nuclear overlapping, irregular nuclei and fine chromatin in all cases; however, nuclear grooves and inclusions were scarce. Galectin-3 immunostaining was performed on the cell blocks of 65 cases and this was positive for 45 cases (69.2%). The results of our study demonstrate that the determination of minimal cytologic criteria is needed to raise the sensitivity of detecting FVPTC by FNAC, and galectin-3 immunostaining is useful to make decisions on the surgical treatment of cytologically atypical thyroid nodules.